Dexmedetomidine attenuates lung apoptosis induced by renal ischemia–reperfusion injury through α(2)AR/PI3K/Akt pathway - Li, Juanjuan (J Transl Med, 2018)
BACKGROUND: Acute lung injury caused by renal ischemia–reperfusion is one of the leading causes of acute kidney injury-related death. Dexmedetomidine, an α(2)-adrenergic agonist sedative, has been found to have protective effects against acute kidney injury and remote lung injury. We sought to determine whether dexmedetomidine can exert its anti-apoptotic effects in acute lung injury after acute kidney injury, in addition to its common anti-inflammatory effects, and to determine the underlying mechanisms. METHODS: In vivo, acute kidney injury was induced by 60 min of kidney ischemia (bilateral occlusion of renal pedicles) followed by 24 h of reperfusion. Mice received dexmedetomidine (25 µg/kg, i.p.) in the absence or presence of α(2)-adrenergic antagonist atipamezole (250 µg/kg, i.p.) before IR. Histological assessment of the lung was conducted by HE staining and arterial blood gases were measured. Lung apoptosis was assessed by terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling assay. The expression of caspase 3 and p-Akt in lung tissue was detected by western blot. In vitro, C57BL/6J mice pulmonary microvascular endothelial cells were treated with serum from mice obtained following sham or IR. Dexmedetomidine was given before serum stimulation in cells, alone or with atipamezole or LY294002. Cell viability was assessed by CCK 8 assay. Cell apoptosis was examined by Hoechst staining and Annexin V-FITC/PI staining flow cytometry analysis. Mitochondrial membrane potential was measured by flow cytometry. The expression of p-Akt, caspase 3, Bcl-2 and Bax was measured by western blot. RESULTS: In vivo, dexmedetomidine remarkably mitigated pathohistological changes and apoptosis and significantly increased p-Akt expression in the lung. In addition, dexmedetomidine also slightly improved oxygenation in mice after IR, which can be abolished by atipamezole. In vitro, dexmedetomidine significantly inhibited IR serum-induced loss of viability and apoptosis in PMVECs. Dexmedetomidine increased p-Akt in a time- and dose-dependent manner, and down-regulated the expression of caspase 3 and Bax and up-regulated the Bcl-2 expression in PMVECs. The changes of MMP were also improved by dexmedetomidine. Whilst these effects were abolished by Atipamezole or LY294002. CONCLUSION: Our results demonstrated that dexmedetomidine attenuates lung apoptosis induced by IR, at least in part, via α(2)AR/PI3K/Akt pathway.